2000
DOI: 10.1002/1098-2795(200007)56:3<412::aid-mrd12>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the role of egg integrins in sperm-egg binding and fusion

Abstract: Sperm‐egg fusion is believed to be mediated via specific molecular interactions. Integrin α6β1 is a strong candidate for a sperm receptor on the egg plasma membrane. However, the ability of the egg integrin α6β1 to interact with molecules on intact sperm has not yet been proven. In this report, possible involvement of integrin α6β1 in sperm‐egg interactions was examined by biochemical and immunocytochemical analyses. To identify egg molecules that specifically interact with sperm, we first incubated sperm with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 59 publications
2
25
0
Order By: Relevance
“…In the mouse (using ZP-free eggs), clustering of integrins at sperm contact and fusion occurred concomitantly, and the percentage of eggs in which the integrin ␣6 and ␤1 subunits appeared clustered at a sperm-binding site was closely correlated to the percentage of eggs with fused sperm. This led Takahashi et al to suggest that sperm-egg fusion occurs at sites where the ␣6␤1 integrin is clustered (Takahashi et al, 2000). In our study, we observed, before fusion, a strong labelling of CD9 and to a lower extent of integrin ␣6␤1 at the site of interaction of the sperm with the oocyte.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the mouse (using ZP-free eggs), clustering of integrins at sperm contact and fusion occurred concomitantly, and the percentage of eggs in which the integrin ␣6 and ␤1 subunits appeared clustered at a sperm-binding site was closely correlated to the percentage of eggs with fused sperm. This led Takahashi et al to suggest that sperm-egg fusion occurs at sites where the ␣6␤1 integrin is clustered (Takahashi et al, 2000). In our study, we observed, before fusion, a strong labelling of CD9 and to a lower extent of integrin ␣6␤1 at the site of interaction of the sperm with the oocyte.…”
Section: Discussionsupporting
confidence: 93%
“…At latter time, the sperm entry point could not be detected based on CD9 and integrin labelling, suggesting that these molecules diffuse rapidly in the plasma membrane after fusion. This result is consistent with the study of Takahashi et al who observed that the ␣6␤1 integrin disappeared from the site of sperm penetration (Takahashi et al, 2000). These data further suggest a role for integrin ␣6␤1 patches during sperm-egg fusion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The first member of the integrin family shown to be active in this regard was a6b1. GoH3, a functionblocking mAb against the a6 integrin subunit, inhibited both sperm -oocyte binding and fusion, and peptides derived from a sequence of a part or all of the fertilin b disintegrin domain bound to a6b1 integrin (Almeida et al 1995, Chen & Sampson 1999, Takahashi et al 2000. However, the contribution of a6b1 integrin to the spermoocyte interaction remains questionable because some inhibition studies using GoH3 mAb under different conditions did not show blocking of the interaction (Evans et al 1997a, Miller et al 2000.…”
Section: Integrins On Oocytes and Adams On Spermmentioning
confidence: 99%
“…The first member of the integrin family shown to be active in sperm-egg fusion was the a6b1 integrin. Hence, GoH3, a function-blocking mAb directed against the a6 integrin subunit, inhibits sperm-oocyte binding and consequently fusion (5,8,9). Recently we showed that a6b1 integrin is also present in mouse sperm and involved in the fertilizing process (10).…”
mentioning
confidence: 99%